Efficacy of Tislelizumab plus Lenvatinib in hepatocellular carcinoma after curative hepatectomy: a real-world study - Chen, Kai; Feng, Xu; Shi, Yuan; Xiao, Heng; Lan, Xiang; Shi, Zheng-Rong (Frontiers in Immunology, 2025)
BackgroundThe efficacy of adjuvant therapy after curative resection for hepatocellular carcinoma (HCC) patients is still debated. This study aimed to evaluate the impact of adjuvant Tislelizumab combined with Lenvatinib on the prognosis of patients with HCC after hepatectomy.MethodsPatients diagnosed with HCC and undergoing curative hepatectomy were retrospectively enrolled, and stratified into two groups: the Hepatectomy alone group and the Hepatectomy−T-L group, based on whether they received adjuvant therapy with Tislelizumab and Lenvatinib. The primary endpoint was disease-free survival (DFS); the secondary endpoints included overall survival (OS) and adverse events.ResultsA total of 288 patients were enrolled and assigned to the Hepatectomy alone group (n=256) and the Hepatectomy−T-L group (n=32) between January 2019 and December 2023. Baseline demographic and clinical characteristics were well balanced between the two groups. The median follow−up time was 28.73 months (95% CI 26.03–31.43 months). The median DFS was significantly longer in the Hepatectomy-T-L group than in the Hepatectomy Alone group [40.78 months (95% CI 29.25–52.31) vs. 28.80 months (95% CI 25.52–32.08), hazard ratio [HR] = 0.51 (95% CI 0.28–0.91), P = 0.021]. The median OS was also significantly longer in the Hepatectomy-T-L group than in the Hepatectomy Alone group [42.10 months (95% CI 37.55–46.65) vs. 34.00 months (95% CI 30.40–37.60), HR = 0.36 (95% CI 0.18–0.70), P = 0.0018]. Adverse events were more frequently observed in the Hepatectomy-T-L group. The incidence of adverse events (AEs) was compared and manageable between the two groups.ConclusionsAdjuvant Tislelizumab and Lenvatinib after curative hepatectomy holds significant potential benefits with manageable adverse events.